Swiss Primary Teachers’ Professional Well-Being During School Closure Due to the COVID-19 Pandemic - Hascher, Tina; Beltman, Susan; Mansfield, Caroline (Frontiers in Psychology, 2021)
During sudden school closures in spring 2020 due to the COVID-19 pandemic, teachers had to move to distance teaching. This unprecedented situation could be expected to influence teacher well-being and schools as organizations. This article reports a qualitative study that aims at understanding how changes in teachers’ professional lives that were related to school closure affected Swiss primary teachers’ professional well-being. In semi-structured online-interviews, 21 teachers from 15 schools sampled by snowball method reported their experiences during school closure and distance teaching and how this situation influenced their professional well-being. Results showed that medium to high levels of teacher well-being could accompany a general negative evaluation of the move to distance teaching. Factors such as high work-load, social distancing and feelings of lack of competence and self-efficacy were among the most aversive aspects of distance teaching and associated with deteriorating professional well-being. Among a plethora of factors that supported teachers in maintaining their well-being, contextual work-related aspects such as school resources, collegial support or leadership support along with individual aspects such as resilience, coping strategies, and clear work structures were important. Additionally, it was found that teacher well-being was nourished by positive experiences with the new forms of distance teaching and feelings of professional mastery. The findings of this study could inform schools and authorities about what is needed to support teacher well-being and might help to develop organizational strategies that aim at preventing harmful declines in teacher well-being during challenging and difficult times such as a pandemic.